Family life and autistic children with sensory processing differences: A qualitative evidence synthesis of occupational participation - Daly, Gina; Jackson, Jeanne; Lynch, Helen (Frontiers in Psychology, 2022)
Autistic children with sensory processing differences successfully navigate and engage in meaningful family daily occupations within home and community environments through the support of their family. To date however, much of the research on autistic children with sensory processing differences, has primarily been deficit focused, while much of the caregiver research has focused on issues of distress, burden, effort, and emotional trauma in coping with their child’s diagnosis. This study aimed to conduct a qualitative evidence synthesis, using a meta-ethnographic approach to explore the gap identified in understanding successful occupational experiences of family participation and daily family routines when supporting an autistic child with sensory processing differences and to offer an alternative strengths-based perspective. Inclusion criteria were studies which were peer-reviewed qualitative design, published from 2000 – 2021, and that concerned parents/caregivers’ perspectives of family occupations of children diagnosed with autism spectrum disorder. Studies were electronically searched in eight databases from October to December 2021 and 23 studies were identified which met the inclusion criteria. Noblit and Hare’s seven step approach for conducting analysis in meta-ethnography was used, and three themes identified: (1) sensory processing differences in daily life, (2) what is hard about hard, and (3) orchestrating family life. Results identified the centrality of sensory experiences in understanding family life. Living with unpredictability while orchestrating certainty through routines was core to successful participation. This review provides insights into how parents negotiate the complexities of constructing family life when living with an autistic child. The results can inform the design of future interventions that specifically address the relationship between meaningful participation in family occupations and daily routines and sensory processing in autistic children.